2019
DOI: 10.3390/su11030822
|View full text |Cite
|
Sign up to set email alerts
|

The Spatiotemporal Coupling Characteristics of Regional Urbanization and Its Influencing Factors: Taking the Yangtze River Delta as an Example

Abstract: The research on the coupling coordination of regional urbanization is of great significance for achieving sustainable urbanization. Based on the theories of coordinated development, this paper constructs an index system for comprehensive evaluation of the three sub-systems of urbanization (population, economy and land urbanization). Then, the entropy method, coupling coordination degree model and spatial autocorrelation analysis are used to explore the spatiotemporal characteristics of overall and pairwise coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…For the calculation of the weight of the indexes, this paper first used the entropy method [57] to calculate the objective weight, the AHP (Analytic Hierarchy Process) [58] method to calculate the subjective weight, and then took the arithmetic mean of both as the final weight. As such, the subjective and objective weights were considered comprehensively.…”
Section: Cut Analysis Methodsmentioning
confidence: 99%
“…For the calculation of the weight of the indexes, this paper first used the entropy method [57] to calculate the objective weight, the AHP (Analytic Hierarchy Process) [58] method to calculate the subjective weight, and then took the arithmetic mean of both as the final weight. As such, the subjective and objective weights were considered comprehensively.…”
Section: Cut Analysis Methodsmentioning
confidence: 99%
“…Apart from developing transportation and other infrastructure and strengthening their industrial development, promoting the growth poles is a better strategy to promote provincial cooperation and achieve a high level of balanced development in the future. The primary task of achieving coupling coordination for these Low-Low areas may still involve the development of the economy [47]. These five cities as the growth poles would drive the economic and social development of the surrounding L-L areas.…”
Section: Discussionmentioning
confidence: 99%
“…Xu studied the coupling coordination relations among population, land, and economic urbanization, and between each pair of them. The research showed that economic urbanization was the main factor affecting the spatial-temporal difference in the overall coupling coordination degree [ 25 ]. Lin discussed the spatial distribution of cities in the process of rapid land urbanization and found that the land urbanization in China showed obvious spatial differences.…”
Section: Literature Reviewmentioning
confidence: 99%